INTERPRETATION OF TASAWWUF IN ISLAMIC EDUCATION TO IMPROVE RELIGIOUS TOLERANCE - Widia Astuti; Muhammad Hafizh; Sarah Dina; Mudzakkir Ali (Islamuna: Jurnal Studi Islam, 2023)
ABSTRAK Problematika riset ini berupa maraknya sejumlah kasus dan isu terkait intoleransi dalam beragama yang terjadi di Indonesia dalam beberapa tahun terakhir ini. Salah satu upaya Kementerian Agama yakni dengan program moderasi beragama yang disosialisasikan melalui internalisasi dalam dunia pendidikan hingga ke masyarakat umum. Penelitian ini menggunakan studi pustaka yang dikategorikan jenis kualitatif. Data diperoleh melalui teknik pengumpulan data dengan dokumen dan dianalisis dengan causal descriptive yang bertujuan untuk mengungkapkan dan mendeskripsikan relevansi pemikiran Syaikh Yusuf al-Makassari dalam Pendidikan Islam sebagai upaya dalam meningkatkan moderasi beragama. Hasil penelitian adalah pemikiran etika tasawuf Syaikh Yusuf al-Makassari dinilai relevan dengan Pendidikan Islam karena orientasi pada rasa dan etika religius yang bersifat adaptif. Pemikiran tersebut sangat menekankan pada nilai-nilai moderasi dan toleransi yang sangat tinggi berupa tawassuth, tawazun, i’tidal dan tasamuh. Nilai-nilai yang sejalan dengan moderasi beragama ini, maka patur diterapkan dalam kehidupan berbangsa dan bernegara khusunya di Indonesia yang majemuk. ABSTRACT The problem with this research is the rise in a number of cases and issues related to religious intolerance that have occurred in Indonesia in recent years. One of the Ministry of Religion's efforts is a religious moderation program that is socialized through internalization in the world of religion. This research used a literature study, which is classified as qualitative. Data were obtained through data collection techniques with documents and analyzed using causal descriptive, which aims to reveal and describe the relevance of Shaykh Yusuf al-Makassari's thoughts in Islamic education as an effort to increase religious moderation. The results of the research show that Syaikh Yusuf al-Makassari's Sufism (tasawwuf) ethical thoughts are considered relevant to Islamic education because of their orientation towards adaptive religious feelings and ethics. These thoughts place great emphasis on the very high values of moderation and tolerance in the form of tawassuth, tawazun, itidal, and tasamuh. These values are in line with religious moderation, so they should be applied in the life of the nation and state, especially in a pluralistic Indonesia.